LeishIF3d is a non-canonical cap-binding protein in Leishmania - Bose, Priyanka; Baron, Nofar; Pullaiahgari, Durgeshwar; Ben-Zvi, Anat; Shapira, Michal (Frontiers in Molecular Biosciences, 2023)
Translation of most cellular mRNAs in eukaryotes proceeds through a cap-dependent pathway, whereby the cap-binding complex, eIF4F, anchors the pre-initiation complex at the 5′ end of mRNAs driving translation initiation. The genome of Leishmania encodes a large repertoire of cap-binding complexes that fulfill a variety of functions possibly involved in survival along the life cycle. However, most of these complexes function in the promastigote life form that resides in the sand fly vector and decrease their activity in amastigotes, the mammalian life form. Here we examined the possibility that LeishIF3d drives translation in Leishmania using alternative pathways. We describe a non-canonical cap-binding activity of LeishIF3d and examine its potential role in driving translation. LeishIF3d is required for translation, as reducing its expression by a hemizygous deletion reduces the translation activity of the LeishIF3d(+/−) mutant cells. Proteomic analysis of the mutant cells highlights the reduced expression of flagellar and cytoskeletal proteins, as reflected in the morphological changes observed in the mutant cells. Targeted mutations in two predicted alpha helices diminish the cap-binding activity of LeishIF3d. Overall, LeishIF3d could serve as a driving force for alternative translation pathways, although it does not seem to offer an alternative pathway for translation in amastigotes.